Curriculum Development Strategy for Independent Learning in Arabic Language Learning at PTKIN in East Java - Danial Hilmi; Nur Toifah; Halimatus Sa`diyah (LISANIA: Journal of Arabic Education and Literature, 2023)
This study aims to analyze the MBKM curriculum development strategy for Arabic learning and its implementation at PTKIN in East Java. The approach used a qualitative approach with a multi-site study in the Arabic language education study program at UIN Maulana Malik Ibrahim Malang and IAIN Kediri which already organized MBKM for learning Arabic. The data obtained in this study are in the form of views of stakeholders or heads of study programs and curriculum documents regarding the implementation of the MBKM program either through guidelines or through websites. The data collection techniques used were interview, observation, and a study through documents on the implementation of learning Arabic. The results of this study concluded that the curriculum development strategy is carried out through the stages of determining graduate achievements, mapping courses, marketing courses based on specialization in teaching assistance and apprenticeships designed with an internship within 6 months at school institutions and apprenticeship institutions, as well as the preparation of lesson plans, and conversion of assistance, internship, and Certificate of Substitute for Diploma for students’ competencies.